Instructional Quality in the Geography Classroom–Derivation and Critical Discussion of an Extended Model - Scholten, Nina; Bienert, Natalie; Mehren, Martina; Mehren, Rainer (Journal of Geography Education, 2024)
The question which features constitute instructional quality is highly relevant, but difficult to answer. Theoretical Abstract models are a way to communicate ideas. Mehren and Mehren (2022) published such a model concerning geography education which will be subjected to an in-depth academic discussion. The derivation of the model shows that the basic structure is adapted from existing models, while its features were predominantly deduced from the debate in geography education. Against the background of general requirements for theoretical models, the subject specificity, the attribution of generic and subject-specific features, the interrelationships and the contribution for teaching and research in geography education are discussed.